DASH Dietary Pattern and Cardiometabolic Outcomes: An Umbrella Review of Systematic Reviews and Meta-Analyses - Chiavaroli, Laura; Viguiliouk, Effie; Nishi, Stephanie K; Blanco Mejia, Sonia; Rahelić, Dario; Kahleová, Hana; Salas-Salvadó, Jordi; Kendall, Cyril Wc; Sievenpiper, John L (Nutrients, 2019)
BACKGROUND: The Dietary Approaches to Stop Hypertension (DASH) dietary pattern, which emphasizes fruit, vegetables, fat-free/low-fat dairy, whole grains, nuts and legumes, and limits saturated fat, cholesterol, red and processed meats, sweets, added sugars, salt and sugar-sweetened beverages, is widely recommended by international diabetes and heart association guidelines. OBJECTIVE: To summarize the available evidence for the update of the European Association of the Study of Diabetes (EASD) guidelines, we conducted an umbrella review of existing systematic reviews and meta-analyses using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach of the relation of the DASH dietary pattern with cardiovascular disease and other cardiometabolic outcomes in prospective cohort studies and its effect on blood pressure and other cardiometabolic risk factors in controlled trials in individuals with and without diabetes. METHODS: MEDLINE and EMBASE were searched through 3 January 2019. We included systematic reviews and meta-analyses assessing the relation of the DASH dietary pattern with cardiometabolic disease outcomes in prospective cohort studies and the effect on cardiometabolic risk factors in randomized and non-randomized controlled trials. Two independent reviewers extracted relevant data and assessed the risk of bias of individual studies. The primary outcome was incident cardiovascular disease (CVD) in the prospective cohort studies and systolic blood pressure in the controlled trials. Secondary outcomes included incident coronary heart disease, stroke, and diabetes in prospective cohort studies and other established cardiometabolic risk factors in controlled trials. If the search did not identify an existing systematic review and meta-analysis on a pre-specified outcome, then we conducted our own systematic review and meta-analysis. The evidence was summarized as risk ratios (RR) for disease incidence outcomes and mean differences (MDs) for risk factor outcomes with 95% confidence intervals (95% CIs). The certainty of the evidence was assessed using GRADE. RESULTS: We identified three systematic reviews and meta-analyses of 15 unique prospective cohort studies (n = 942,140) and four systematic reviews and meta-analyses of 31 unique controlled trials (n = 4,414) across outcomes. We conducted our own systematic review and meta-analysis of 2 controlled trials (n = 65) for HbA1c. The DASH dietary pattern was associated with decreased incident cardiovascular disease (RR, 0.80 (0.76⁻0.85)), coronary heart disease (0.79 (0.71⁻0.88)), stroke (0.81 (0.72⁻0.92)), and diabetes (0.82 (0.74⁻0.92)) in prospective cohort studies and decreased systolic (MD, -5.2 mmHg (95% CI, -7.0 to -3.4)) and diastolic (-2.60 mmHg (-3.50 to -1.70)) blood pressure, Total-C (-0.20 mmol/L (-0.31 to -0.10)), LDL-C (-0.10 mmol/L (-0.20 to -0.01)), HbA1c (-0.53% (-0.62, -0.43)), fasting blood insulin (-0.15 μU/mL (-0.22 to -0.08)), and body weight (-1.42 kg (-2.03 to -0.82)) in controlled trials. There was no effect on HDL-C, triglycerides, fasting blood glucose, HOMA-IR, or CRP. The certainty of the evidence was moderate for SBP and low for CVD incidence and ranged from very low to moderate for the secondary outcomes. CONCLUSIONS: Current evidence allows for the conclusion that the DASH dietary pattern is associated with decreased incidence of cardiovascular disease and improves blood pressure with evidence of other cardiometabolic advantages in people with and without diabetes. More research is needed to improve the certainty of the estimates.
Keywords: review; dietary approaches to stop hypertension; DASH; Hypertension; DASH dieta; Dietary Approaches To Stop Hypertension; GRADE; Systematic Reviews as Topic; cardiometabolic health; Cardiovascular Diseases; Humans; systematický přehled jako téma; metabolické nemoci; hypertenze; Metabolic Diseases; cardiovascular disease; Meta-Analysis as Topic; metaanalýza jako téma; kardiovaskulární nemoci; lidé